Pengaruh Model Project Based Learning terhadap Kemampuan Membaca Artikel Penelitian Mahasiswa Biologi - Dian Tauhidah; Herawati Susilo; Hadi Suwono (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This study aims to determine there is a difference in the ability to read student research articles through the application of project based learning model. This research is a quasi experimental research with nonequivalent study of pretest-posttest control group design. The population used is all biology students of Malang State University. The samples used were 85 students divided into three classes: negative control, positive control, and experiment. The research instrument used in the form of a description test developed from Lacum’s (2004) rethorical moves: motives, objective, novelty, main conclusion, support, counterargument, refutation, and implication. The results were analyzed using ANACOVA statistic test. The results showed F count 0.00 <0.05 which means there is a difference in the ability to read research articles through the application of project based learning model.Abstrak: Penelitian ini bertujuan untuk mengetahui ada beda kemampuan membaca artikel penelitian mahasiswa melalui penerapan model project based learning. Penelitian ini merupakan penelitian kuasi eksperimen dengan rancangan penelitian nonequivalent pretest-posttest control group design. Populasi yang digunakan adalah seluruh mahasiswa Biologi Universitas Negeri Malang. Sampel yang digunakan adalah 85 mahasiswa yang terbagi menjadi tiga kelas yaitu kelas kontrol negatif, kontrol positif, dan eksperimen. Instrumen penelitian yang digunakan berupa tes uraian yang dikembangkan dari aspek rethorical moves milik Lacum (2004) yaitu motives, objective, novelty, main conclusion, support, counterargument, refutation, dan implication. Hasil penelitian dianalisis menggunakan uji statistik ANACOVA. Hasil penelitian menunjukkan F hitung 0,00 < 0,05 yang berarti ada perbedaan kemampuan membaca artikel penelitian melalui penerapan model project based learning.